2020
DOI: 10.1038/s41437-020-0344-6
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic features and limited dispersal shape the population genetic structure of the vase sponge Ircinia campana in the Greater Caribbean

Abstract: Understanding population genetic structure can help us to infer dispersal patterns, predict population resilience and design effective management strategies. For sessile species with limited dispersal, this is especially pertinent because genetic diversity and connectivity are key aspects of their resilience to environmental stressors. Here, we describe the population structure of Ircinia campana, a common Caribbean sponge subject to mass mortalities and disease. Microsatellites were used to genotype 440 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 97 publications
4
11
0
Order By: Relevance
“…The results of Griffiths et al (2021) and our current study are congruent in that Panamanian I. campana and Floridian I. campana appear in different clusters. Given their observations, Griffiths et al (2021) suggested that I. campana might represent a case of cryptic speciation, although they restrict this proposal to a population inhabiting the Sapodilla Cayes that appeared particularly divergent from the remaining clusters. Given our BFD * results, we would like to append that cryptic speciation in I. campana, which curiously tracks microbiome divergence, could be a phenomenon that encompasses populations in addition to the one at Sapodilla Cayes.…”
Section: Hidden Species Richness Of Caribbean Irciniasupporting
confidence: 87%
See 2 more Smart Citations
“…The results of Griffiths et al (2021) and our current study are congruent in that Panamanian I. campana and Floridian I. campana appear in different clusters. Given their observations, Griffiths et al (2021) suggested that I. campana might represent a case of cryptic speciation, although they restrict this proposal to a population inhabiting the Sapodilla Cayes that appeared particularly divergent from the remaining clusters. Given our BFD * results, we would like to append that cryptic speciation in I. campana, which curiously tracks microbiome divergence, could be a phenomenon that encompasses populations in addition to the one at Sapodilla Cayes.…”
Section: Hidden Species Richness Of Caribbean Irciniasupporting
confidence: 87%
“…The polyphyly of I. campana is a result that departs from conventional knowledge about this species, which is typically regarded as monophyletic and is one of the Ircinia in the Caribbean whose gross phenotypic features are expected to track species boundaries. Interestingly, a recent publication (Griffiths et al, 2021) used microsatellite genotyping of host sponges to uncover a trend of high genetic population structure among geographically distant I. campana populations, which were found to constitute four distinct admixture clusters. The results of Griffiths et al (2021) and our current study are congruent in that Panamanian I. campana and Floridian I. campana appear in different clusters.…”
Section: Hidden Species Richness Of Caribbean Irciniamentioning
confidence: 99%
See 1 more Smart Citation
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in highly diversified chemical natures [3][4][5][6]. The marine ecosystems of Martinique are rich in sponges [7][8][9][10][11][12], however, they are undervalued [13]. The aim of this study is to increase our knowledge of Martinique's sponges and their potential antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Marine sponges produce abundant secondary biomolecules and have highly diversified chemical natures [3-6]. The marine ecosystems of Martinique are rich in sponges [7–12], however, they are undervalued [13]. The aim of this study is to increase our knowledge of Martinique’s sponges and their potential antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%